Experimentation and Job Choice - Antonovics, Kate; Golan, Limor (Journal of Labor Economics, 2012)
In this article, we examine optimal job choices when jobs differ in the rate at which they reveal information about workers’ skills. We then analyze how the optimal level of experimentation changes over a worker’s career and characterize job transitions and wage growth over the life cycle. Using the Dictionary of Occupational Titles merged with the National Longitudinal Survey of Youth 1979, we then construct an index of how much information different occupations reveal about workers’ skills and document patterns of occupational choice and wage growth that are consistent with a trade-off between information and wages.